Solubility enhancement and structural insights into pipemidic acid via salt formation with benzoic acid - Chandrashekar, Shwetha Jayapura; Eswaramoorthy, Rajalakshmanan; Solomon, Kamalakaran Anand (European Journal of Chemistry, 2025)
Pipemidic acid (PMA) is an active pharmaceutical ingredient (API) belonging to the quinolone class of antibacterial agents, primarily used to treat urinary tract infections. This study investigated improving the dissolution properties of poorly soluble PMA by forming a 1:1 stoichiometry molecular salt (4BA) with benzoic acid (BA). Liquid-assisted grinding and slow evaporation techniques were used to prepare the solid form of the salt. The salt was then characterized using differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and single-crystal X-ray diffraction (SC-XRD). The DSC analysis provided information on the changes in thermal behavior associated with the formation of the salt. FTIR spectroscopy helped identify the functional groups present and potential interactions between PMA and benzoic acid. SC-XRD determined the definitive three-dimensional arrangement of atoms within the salt structure, revealing a wave-like hydrogen bonding network directing a 3D layered packing of molecules. This improved packing is believed to be responsible for the improved solubility of PMA in the salt form. The Hirshfeld surface analysis, along with its associated 2D fingerprint plots, further elucidated the intermolecular interactions within the crystal lattice. This analysis showed that, in addition to the strong N-H···O and O-H···O hydrogen bonds, weaker H···H, C···H, and H···C interactions also play a significant role in stabilizing the molecular packing. Finally, cumulative drug release (CDR) showed that the formation of the molecular salt significantly improved the dissolution behavior of PMA, potentially leading to sustained drug release.